2002
DOI: 10.1128/jvi.76.13.6442-6452.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope Glycoprotein of Human Endogenous Retrovirus Type W Uses a Divergent Family of Amino Acid Transporters/Cell Surface Receptors

Abstract: The human endogenous retrovirus type W (HERV-W) family includes proviruses with intact protein-coding regions that appear to be under selection pressure, suggesting that some HERV-W proviruses may remain active in higher primates. The envelope glycoprotein (Env) encoded by HERV-W is highly fusogenic, is naturally expressed in human placental syncytiatrophoblasts, and has been reported to function as a superantigen in lymphocyte cultures. Recent evidence suggested that HERV-W Env can mediate syncytium formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 62 publications
7
157
0
3
Order By: Relevance
“…Syncytin, the envelope protein of one of the defective HERV-W proviruses is obviously essential for the formation and function of syncytiotrophoblasts (84)(85)(86)(87). These multinucleated cells originate from fetal trophoblasts and constitute the boundary layer between maternal and fetal tissue.…”
Section: Biological Implications Of Retroelement Inheritancementioning
confidence: 99%
“…Syncytin, the envelope protein of one of the defective HERV-W proviruses is obviously essential for the formation and function of syncytiotrophoblasts (84)(85)(86)(87). These multinucleated cells originate from fetal trophoblasts and constitute the boundary layer between maternal and fetal tissue.…”
Section: Biological Implications Of Retroelement Inheritancementioning
confidence: 99%
“…Inhibition of the trophoblast invasion may lead to diseases like preeclampsia; uncontrolled invasion may lead to placenta accreta, increta or even percreta ( [Knerr et al, 2002] and [Lavillette et al, 2002]). …”
Section: Potential Immunosuppressive Function Of Herv-k In the Placentamentioning
confidence: 99%
“…In addition, ERV-3 ( [Boyd et al, 1993] and [Venables et al, 1995]) and HERV-E (Yi and Kim, 2007) were also found to be expressed in placental tissue. While syncytin-1 interacts with the D type mammalian retrovirus receptor (ASCT2) ( [Blond et al, 2000] and [Lavillette et al, 2002]), which is mainly expressed in VT cells (Hayward et al, 2007), the receptor of syncytin-2 (MFSD2) is specifically expressed in the syncytiotrophoblast (Esnault et al, 2008). Syncytin-1 was shown to mediate the fusion of the villous cytotrophoblast to form the multinucleated syncytiotrophoblast ( [Blond et al, 2000] and [Frendo et al, 2003]).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several transporters also function as receptors for different neurotropic retroviruses (4). The human endogenous retrovirus (HERV-W) envelope glycoprotein, Syncytin-1, binds to two receptors including the sodium-dependent transporters of polar neutral amino acids, alanine, serine, cysteine, and threonine (ASCT1 and ASCT2) (4), which are localized on both neurons and glia (5) and are known to modulate both neurotrophic (6) and neurotoxic (7) effects in the CNS.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%